SIMULASI MONTE CARLO DENGAN MODEL PERSEDIAAN STOKASTIK PADA PT.BINGEI MEDAN - Simamora, Roni Jhonson; Jamaluddin (JTIK (Jurnal Teknik Informatika Kaputama), 2017)
Inventory systems or inventory is very important for a company, especially if the company is engaged in the distribution of goods. PT. Bingei Medan is a company engaged in the sale of fertilizers. The availability of fertilizers in fulfilling customer orders to be very important, it is necessary to well-managed inventory. The purpose of this study is to make simulation using the programming language Microsoft Visual Basic Version 6.0 and simulations built a simulation model of the stochastic inventory system PT. Bingei Medan. And the results of this simulation to analyze the characteristics of inventory system such as the average level of availability of goods, the amount of goods ordered, the number of items that are not fulfilled (stock out) and the amount of time ordering goods